An analysis of the cultivation, consumption and composition of home-grown cannabis following decriminalisation in the Australian Capital Territory - Cilla Zhou; Isobel Lavender; Rebecca Gordon; Danielle McCartney; Richard C. Kevin; Miguel A. Bedoya-Pérez; Iain S. McGregor (Scientific Reports)
Abstract The Australian Capital Territory (ACT), a region that includes Australia’s capital, Canberra, decriminalised small-scale cannabis cultivation and possession in January 2020. Here, we examined cannabis use and cultivation behaviours, experiences and attitudes of current and past small-scale ACT cannabis cultivators. ACT residents (n = 311) who currently cultivate or have previously cultivated cannabis completed a cross-sectional online survey (‘CAN-ACT’) and provided home-grown cannabis for phytocannabinoid analysis (optional). Reasons for cultivation included a preference for home-grown cannabis to self-supply, enjoyment of the process and avoiding criminal networks. Cannabis intake was a median of 1 gram on a typical day used and the number of plants grown per year was a median of 4. Various cultivation challenges were identified, most commonly mould, nutrient deficiency and spider mites. Cannabis samples (n = 71) generally exhibited moderate THC content (mean 8.99 ± SEM 0.51% [w/w]) and low CBD content (< 0.1%). Few samples exceeded contaminant guidelines for heavy metals or pesticides. Respondents identified various grey areas in current legislation that might lead to inadvertent criminal activity, and many (52%) remained anxious about arrest. In general, recent legislative changes appear to support community needs. Options for further legislative refinement are discussed.